ANALISIS KOREKSI FISKAL TERHADAP LAPORAN KEUANGAN PADA PT KUBAR OUTSOURCE GLOBAL - Ishak Iskandar Dinata; Raden Priyo Utomo (AKUNTABEL, 2015)
This research was performed at PT Kubar Outsource Global with the aim to analyze and determine whether the fiscal correction which has been carried out by PT Kubar Outsource Global accordance with the tax regulations in Indonesia. The financial statements  of  the  company  are  prepared  in  accordance  with  Accounting  Standards,  however  to  do  the calculation of corporate taxes should consider the rules of applicable taxes. This regulation is called the Fiscal Reconciliation. The results of this study indicate that in the preparation of the Income Statement, PT Kubar Outsource Global experienced an error correction in loading the depreciation of fixed assets, contribution, and the fiscally medical cost, Furthermore the base of the corporate taxes rate is also  not conform with the laws and regulations that will have an impact on profit an income tax produce by the company. According to the company, the  profit  before tax is  62,321,891.45 that the  income tax  is  15,580,472.86. According to  the regulation the profit before tax is 78,126,391.45 that the income tax is 9,765,798.93. Keywords : Fiscal Reconciliation, Analysis of Fiscal Correction